2005
DOI: 10.1111/j.1365-2028.2005.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Stand structure, species diversity and regeneration of an endemic palm forest on the Seychelles

Abstract: The ‘Vallée de Mai’ on the island of Praslin in the Seychelles group is a World Heritage Site because of its unique forest vegetation dominated by the palm Lodoicea maldivica. However, despite its great conservation importance, the stand structure, species diversity and regeneration of this forest have not previously been studied. Moreover, the conservation value of the reserve is currently threatened by invading alien plants and limited regeneration of some native species. The species composition of the fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…The granitic islands are of Pre-Cambrian age (Miller and Mudie 1961) and, because of their long isolation, they are classified as 'Oceanic islands' although of continental origin (Baker and Miller 1963). The flora of the granitic islands of the Seychelles comprises many endemic species (Swabey 1970;Fleischmann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The granitic islands are of Pre-Cambrian age (Miller and Mudie 1961) and, because of their long isolation, they are classified as 'Oceanic islands' although of continental origin (Baker and Miller 1963). The flora of the granitic islands of the Seychelles comprises many endemic species (Swabey 1970;Fleischmann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such species may be less vulnerable to short-term demographic stochasticity, and their longevity and naturally low regeneration over long periods may result in underestimates of population viability where only adult tree counts are used for population estimates (e.g. Fleischmann et al, 2005). However, life history and demography vary considerably among oceanic island plants: not all are slow-growing and long-lived (e.g.…”
mentioning
confidence: 99%
“…The first, a re-survey of six permanent monitoring plots (20 m × 20 m; see Fleischmann et al, 2005) showed that over a period of 24 years eight of 35 L. maldivica died, resulting in a annual mortality rate of ca. 1%.…”
Section: Modelling Population Dynamicsmentioning
confidence: 99%
“…As an estimate of fecundity (annual contribution of each female palm to the next generation), we used data for 407 female trees in six permanent monitoring plots (Fleischmann et al, 2005) and along transects (total length 3.48 km) spanning the entire VM (Fleischer-Dogley, 2006). In the model, mean annual nut production (1.2 nuts/tree) was adjusted for germination success, loss due to harvesting and for the dioecious nature of the palm.…”
Section: Modelling Population Dynamicsmentioning
confidence: 99%